Potencial da inclusão de ração de frango e inoculantes probióticos comerciais na alimentação de larvas de mosca-soldado-negra (Hermetia illucens) - Isabela Parolis Martins (2023)
Based on projections of global population growth, an increase in food production is expected by the year 2050. In light of this scenario, there is ongoing investigation into insects as a sustainable option. The Black Soldier Fly, known as Hermetia illucens, stands out in this context. Accordingly, the present study had two objectives: to evaluate levels of inclusion of chicken feed in the diet of Black Soldier Fly larvae during the nursery phase, and to assess the inclusion of fermentative probiotic inoculants in the diet of larvae during the fattening phase. The first experiment involved the inclusion of different levels of initial chicken feed in the base diet, ranging from 0% to 40%, with intervals of 5%. Neonates were kept on these diets for 5 days under controlled temperature and humidity conditions. After this period, they were separated from the frass, and data were collected. The results were subjected to analysis of variance and Tukey's test at a 5% significance level using R software. The findings showed that larvae fed with 30% and 40% inclusion of chicken feed achieved higher weight gain compared to other treatments (0.051±0.01 and 0.049±0.01, respectively). Regarding frass, the recovered amount after larval removal relative to the amount of food provided ranged from 31.8% (D30%) to 55.8% (D20%), falling within the recommended range (between 30 and 50%). It was concluded that the 30% inclusion rate yielded the best results, with heavier larvae and better utilization of the provided diet. In the second experiment, a diet composed of lemon, wheat bran, and feed mill sweepings was used. Treatments included inoculation with bokashi, compost accelerator, and fermented treatment without inoculant. The treatments were kept in sealed barrels for 21 days before being distributed into production boxes, with 2,400 larvae per replication. The results were analyzed using analysis of variance and Tukey's test at a 5% significance level with R software, showing that larvae fed diets inoculated with 0.5% bokashi, 1% bokashi, and 0.025% compost accelerator exhibited higher weight gain, greater larval biomass harvest at the end of the period, and frass recovery. The control treatment without inoculant outperformed the fermented treatment with 0.05% compost accelerator inclusion. It was concluded that the 30% inclusion rate yielded the best results in terms of heavier larvae and better utilization of the provided diet. Additionally, it was concluded that bokashi inoculation, at the tested levels, as well as compost accelerator inclusion at 0.025%, appear to be promising technologies in Black Soldier Fly larval nutrition.